THE EFFECT OF WORK COMMITMENT, DOWNSIZING, ROLE AMBIGUITY ON EMPLOYEE PERFORMANCE MODERATED BY DIGITAL INVOLVEMENT IN BKKBN REPRESENTATIVES NORTH SUMATRA PROVINCE - Yohanna Yunitha Simangunsong; Rita F. Dalimunthe; Parapat Gultom (RADJA PUBLIKA, 2023)
This research was motivated by the conditions that occurred at the BKKBN Representative of North Sumatra Province after downsizing as a result of the merger of agencies within the local government. Employee performance has decreased fluctuatively. digital involvement that is still lacking so that it demands high employee commitment. The purpose of this study was to determine and analyze the effect of work commitment, downsizing, work ambiguity on employee performance moderated by digital involvement at the BKKBN Representative of North Sumatra Province. Data collection in this study was conducted through a survey approach by distributing questionnaires. The population of this study were 257 family planning extension civil servants. The number of research samples was 195 people. The type of research conducted is descriptive quantitative using a causality approach. The data analysis method in this study uses SEM which is operated through the SmartPLS program. The results showed that work commitment has a positive and significant effect on the performance of employees of the BKKBN Representative of North Sumatra Province. Role ambiguity has a negative but insignificant effect on the performance of employees of the BKKBN Representative of North Sumatra Province. Downsizing has a positive and significant effect on the performance of employees of the BKKBN Representative of North Sumatra Province. Digital engagement weakens and does not significantly affect work commitment to the performance of employees of the BKKBN Representative of North Sumatra Province. Digital engagement weakens and does not significantly affect role ambiguity on the performance of employees of the BKKBN Representative of North Sumatra Province. Digital engagement weakens and significantly affects downsizing on the performance of employees of the BKKBN Representative of North Sumatra Province.